Avaliação da qualidade ambiental nas nascentes do Rio Monjolinho na porção à montante da Estação de Captação de Água do Espraiado, São Carlos - SP - Souza, Amanda Baldochi (2011)
The unplanned development of urban communities strongly contributes to degradation of water resources, jeopardazing the quality of the water and the integrity of aquatic environments. The objetive of the present study was to evaluate the environmental quality of the water sources of River Monjolinho, located upstream the Water Pumping Station of Espraiado. Samplings were carried out in springs and afluent streams to Monjolinho River during two opposite climatic seasons, the rainy and the dry periods between 2009 and 2010. Physical and chemical analyses of water and sediment, ecotoxicological tests with Ceriodaphnia silvestrii and Hyalella meinerti were performed for these two compartments. The benthic macroinvertebrates and diatom communities were analysed in order to evaluate the environmental quality of all these sites. These data were used in different approaches: diversity indices, the biotic index BMWP, multivariate analyses and the Environmental Quality Triad. The water from São Rafael Stream, and the sediments of Cascavel, Middle Monjolinho, Ponte de Tábua and São Rafael streams collected at different sites and sampling periods were toxic to the aquatic biota. The benthic macroinvertebrates community and diatoms analyses evidenced that there are strong differences in the environmental quality between springs and affluents from left margin and those from right margin of Monjolinho River as a result of riparian forest removal or due to the type of soil use: urbanization or agriculture. Restoration measures in the headwaters of São Rafael Stream started by the Municipal Prefecture of São Carlos did not result in better environment quality and rather evidenced a strong contamination. Besides this site, the springs of Belvedere and Ponte de Tábua streams are the river stretches where the strongest impacts swere verified, however, all springs and streams upstream the Espraiado Water Supply Pumping Station need special attention from local government due to the low quality of its waters, exception of the Espraiado Stream.